Early Life Environment and Adult Height: The Case of Chile - Droller, F (Elsevier B.V., 2019)
In this paper, we analyze the relationship between adult height and early-life disease environment, proxied by the infant mortality rate (IMR) in the first year of life, using cohort-region level data for Chile for 1960–1989. IMRs show a remarkable reduction of 100 points per thousand over this thirty-year period, declining from 119.4 to 21.0 per thousand. We also document a 0.96 cm increase in height per decade.We find that the drop in IMRs observed among our cohorts explains almost all of the long-term trend in rising adult heights, and that per capita GDP does not appear to have any predictive power in this context. Results are robust in a variety of specifications, which include area and cohort dummies, an adjustment for internal migration, and urbanization rates. Our results point to the long-term effect of a public health policy. © 2018 Elsevier B.V.